2008
DOI: 10.1073/pnas.0710305105
|View full text |Cite
|
Sign up to set email alerts
|

cis -Jasmone induces Arabidopsis genes that affect the chemical ecology of multitrophic interactions with aphids and their parasitoids

Abstract: It is of adaptive value for a plant to prepare its defenses when a threat is detected, and certain plant volatiles associated with insect damage, such as cis-jasmone (CJ), are known to switch-on defense metabolism. We used aphid and aphid parasitoid responses to Arabidopsis thaliana as a model system for studying gene expression and defense chemistry and its impact at different trophic levels. Differential responses to volatiles of induced Arabidopsis occurred for specialist and generalist insects: the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
154
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 47 publications
2
154
1
1
Order By: Relevance
“…Application of methyl jasmonate, methyl linolenate (MeLin, a precursor of JA), and cisjasmone also attracts natural enemies by inducing volatile production (e.g. Ozawa et al 2004Ozawa et al , 2008Bruce et al 2008). Furthermore, herbivore performance is negatively affected by JA and cis-jasmone treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Application of methyl jasmonate, methyl linolenate (MeLin, a precursor of JA), and cisjasmone also attracts natural enemies by inducing volatile production (e.g. Ozawa et al 2004Ozawa et al , 2008Bruce et al 2008). Furthermore, herbivore performance is negatively affected by JA and cis-jasmone treatments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids can in some cases upregulate genes associated with JA signaling (Thompson and Goggin, 2006;Gao et al, 2007;Kusnierczyk et al, 2007;Kuśnierczyk et al, 2008), and several studies suggest that JA-dependent defenses hinder aphid infestation. Artificial JA treatment enhances aphid resistance in several plant species (Omer et al, 2001;Bruce et al, 2003Bruce et al, , 2008Zhu-Salzman et al, 2004;Cooper and Goggin, 2005); furthermore, aphid population growth on Arabidopsis is enhanced by the coi1 mutation, which inhibits JA perception, and is suppressed by the cev1 mutation, which promotes constitutive JA and ethylene signaling (Ellis et al, 2002;Mewis et al, 2005). On the other hand, there is evidence that SA also contributes to plant defenses against aphids, in contrast to its putative role as a decoy response in interactions between whiteflies and Arabidopsis.…”
mentioning
confidence: 99%
“…For example, in wind tunnel studies, A. ervi was attracted to vapor exposure of CJ-treated Vicia faba plants (Birkett et al, 2000). Moreover, plant defenses induced by CJ in Arabidopsis attracted A. ervi, a generalist aphid parasitoid, but had no influence on Diaeretiella rapae, a specialist aphid parasitoid (Bruce et al, 2008 (2012) found that HIPVs released from CJ-applied Capsicum annum plants were preferred by A. ervi and encouraged its foraging time. To our knowledge, the present study is the first report of aphid parasitoid responses to MEJA under field conditions.…”
Section: Aphid Parasitoidsmentioning
confidence: 99%